Application of evolutionary programming for solving hydrothermal coordination / Mohd Zaini Abd Ghani - Abd Ghani, Mohd Zaini (2003)
This paper describes an efficient method of solving Hydro Thermal Coordination using Evolutionary Programming (EP) method within C programming language. This study focused to determine a schedule for the hydro and thermal generation, which will minimize the total production cost while balancing the generation with demand. Using LaGrange method will compare the results obtained using EP method.